Can we use GIS as a historic city's heritage management system? the case study of Hermoupolis-Syros - Chatzigrigoriou, Pavlos (My University, 2016)
Because of the severe economic crisis, Greek historic heritage is in risk. Historic cities as Hermoupolis, were dealing with this risk years before the crisis. The current situation needed drastic action, with innovative low cost ideas. The historic building stock in Hermoupolis counts more than 1.200 buildings. By recording the pathology, the GIS and the D.B.M.S "HERMeS" with the appropriate algorithms identify the historic buildings in risk. In the first application of the system those buildings were 160, with a rate of 2.4 historic buildings collapse every year. The prioritization of interventions in these buildings is critical, as it is not possible to lower the collapsing risk simultaneously in 160 buildings, but neither the interventions can be judged solely by the reactions of local residents. Bearing in mind the fact that one, given the current economic conditions, has to make best use of the funds for this purpose, it is proved that the relevant decision requires multi criteria analysis method of prioritizing interventions. Specifically, the analysis takes into account the risk of collapse of each building, but in connection with a series of other variables, such as the role of building in Hermoupolis, the position in the city, the influence in other areas of interest, the social impact etc. The final result is a catalogue with historic buildings and a point system, which reflects the risk of loosing the building. The point system leads to a Conservation Plan for the city of Hermoupolis, giving the hierarchy of interventions that must be done in order to save the maximum architecture heritage with the minimum funds, postponing the risk of collapsing. In 2015, EU and EUROPA-NOSTRA awarded the above-mentioned project in the category of "Research and Digitization".
Keywords: Digital heritage; GIS; HERMES; Historic cities